Valuing Mortality and Morbidity in the Context of Disaster Risks - L. Cropper, Maureen (2012)
Benefit-cost analyses of disaster risk reduction (DRR) projects are an important tool for evaluating the efficiency of such projects, and an important input into decision making. These analyses, however, often fail to monetize the benefits of reduced death and injury. The authors review the literature on valuing reduced death and injury, and suggest methods for calculating order-of-magnitude estimates of these benefits. Because few empirical estimates of the Value of a Statistical Life (VSL) are available for developing countries, methods for transferring estimates from high income to middle and low income countries are reviewed. The authors suggest using the range of values implied by an income elasticity of 1.0 and an elasticity of 1.5. With regard to injury valuation they discuss arguments for and against monetizing Quality Adjusted Life Years, and provide shortcuts to valuing injuries that may be used to assess their importance in DRR benefit-cost analyses.